Providing health care to improve community perceptions of protected areas. Issue 4 (11th August 2014) - Chapman, Colin A.; van Bavel, Bianca; Boodman, Carl; Ghai, Ria R.; Gogarten, Jan F.; Hartter, Joel; Mechak, Lauren E.; Omeja, Patrick A.; Poonawala, Sofia; Tuli, Dan; Goldberg, Tony L.
Abstract: Impoverished communities often turn to illegal extraction of resources from protected areas to alleviate economic pressures or to make monetary gains. Such practices can cause ecological damage and threaten animal populations. These communities also often face a high disease burden and typically do not have access to affordable health care. Here we argue that these two seemingly separate challenges may have a common solution. In particular, providing health care to communities adjacent to protected areas may be an efficient and effective way to reduce the disease burden while also improving local perceptions about protected areas, potentially reducing illegal extraction. We present a case study of a health centre on the edge of Kibale National Park, Uganda. The centre has provided care to c. 7, 200 people since 2008 and its outreach programme extends to c. 4, 500 schoolchildren each year. Contrasting the provision of health care to other means of improving community perceptions of protected areas suggests that health clinics have potential as a conservation tool in some situations and should be considered in future efforts to manage protected areas.